2018
DOI: 10.1021/acsaem.8b00077
|View full text |Cite
|
Sign up to set email alerts
|

First-Principles Study of Oxyhydride H Ion Conductors: Toward Facile Anion Conduction in Oxide-Based Materials

Abstract: H − ion conductor materials have the great potential to enable high-energy density electrochemical storage based on hydrogen. Fast H − conduction has been recently demonstrated in the La 2−x−y Sr x+y LiH 1−x+y O 3−y oxyhydride materials.However, little is known about the H − diffusion mechanism in this new material and its unique structure. The origin of such exceptional H − conduction in the oxide-based materials is of great interest. Using first-principles calculations, we studied the energetics and diffusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
48
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(52 citation statements)
references
References 54 publications
4
48
0
Order By: Relevance
“…This complies well with reported results from QENS, where no dynamical behaviour was observed in the temperature range where Kobayashi et al observed hydride anion diffusion [1,2]. In addition, AIMD calculations suggest absence of hydride anion diffusion without vacancies present in the system [10]. Together, this suggests a possible discrepancy in the vacancy concentration for orthorhombic La 2 LiHO 3 synthesized by the high-pressure method as this compound is reported to display hydride anion conductivity [1].…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…This complies well with reported results from QENS, where no dynamical behaviour was observed in the temperature range where Kobayashi et al observed hydride anion diffusion [1,2]. In addition, AIMD calculations suggest absence of hydride anion diffusion without vacancies present in the system [10]. Together, this suggests a possible discrepancy in the vacancy concentration for orthorhombic La 2 LiHO 3 synthesized by the high-pressure method as this compound is reported to display hydride anion conductivity [1].…”
Section: Resultssupporting
confidence: 90%
“…Furthermore, a large vacancy population is a key to promote hydride anion diffusion in the perovskite layer of La 2 LiHO 3 . Our findings are supported by previous reports using QENS and AIMD [2,10]. By comparing, across the entire temperature range, the measured SD of the hydride anion momentum distribution in La 2 LiHO 3 with the prediction for free, non-interacting particles, we predict the onset of a diffusive regime close to the decomposition temperature, a phenomenon which was previously observed by QENS [2].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The defect layer was modelled in a supercell consisting of two slabs of LLTO and two defect layers using the periodic boundary condition (CIF file attached as Supplementary Data 1). From the disordered structure of LLTO and the defect layer from experiments, the atomistic configuration of Li, La, and Ti in the supercell models was generated in a two-step process by comparing and ranking distinctive configurations using the scheme as in our previous work 64 according to electrostatic energies and DFT energies: (1) the atomistic configuration with the lowest GGA energy was selected from the DFT calculations on 100 distinctive configurations, which were obtained according to the minimum electrostatic energy out of 10000 symmetrically distinctive configurations using pymatgen 65 ; (2) the same process was repeated for ordering the atomistic configuration in the 2D defect layers to obtain a low-energy structure model of the defect for further calculations. The NEB calculations were performed with the supercell model of 11.83Å x 11.75Å x 31.84Å containing 378 atoms (detailed structure described in the CIF file attached as Supplementary Data 1).…”
Section: Methodsmentioning
confidence: 99%
“…In studies of SICs, AIMD simulations are performed to directly observe migration events, which are then provided as input for NEB calculations. [33][34][35][36][37] The results from AIMD simulations, together with the energy barriers for specific ion migration pathways from NEB calculations, provide detailed, atomistic-level information on ion diffusion.…”
Section: Ab Initio Molecular Dynamics Simulationmentioning
confidence: 99%